Linking cardiometabolic multimorbidity to depressive symptoms in the oldest-old: results from a cross-sectional study in Germany - Maschke, Verena; Lohner, Valerie; Mons, Ute (BMC public health, 2025)
Background Depression often accompanies cardiometabolic multimorbidity (CMM), but it remains unclear whether this association persists in very old people. Hence, we examined the link between CMM and depressive symptoms in an oldest-old population. Methods Using cross-sectional data from a representative sample of individuals aged 80 years and older in North Rhine-Westphalia, Germany ( N = 1,863), we constructed an additive disease index covering seven cardiometabolic diseases (CMDs): myocardial infarction, heart failure, hypertension, stroke, diabetes mellitus, kidney disease, and obesity. Depressive symptoms were assessed using the short form of the Depression in Old Age Scale (0 to 4 points). We employed multivariable linear regression models to study associations of CMD index (0, 1, 2, ≥ 3 CMDs) and CMD count (0 to 7 diseases) with depressive symptoms, adjusting for age, sex, socio-economic index, respiratory and pulmonary disease, cancer, and liver disease. Results Participants had a mean depressive symptom score of 0.94, and 44% reported two or more CMDs. Heart failure, hypertension, stroke, and obesity were each individually associated with more depressive symptoms. Participants with two (β = 0.30; 95%-CI: 0.12–0.48), and three or more CMDs (β = 0.40; 95%-CI: 0.18–0.62) showed higher depressive symptoms compared to those with no CMD, i.e., each additional CMD was associated with a 0.30-unit or 0.40-unit increase in depressive symptoms, respectively. We observed an additive dose–response association between CMD count and depressive symptoms (β = 0.16; 95%-CI: 0.09–0.23), slightly more pronounced for women (β = 0.19; 95%-CI: 0.10–0.29) than for men (β = 0.10, 95%-CI: 0.02–0.19). Conclusions Individuals with CMM showed increased depressive symptomatology, indicating the need to address both physical and mental health in oldest-old individuals with high CMD burden. However, the cross-sectional study design prevents conclusions about causality and warrants further longitudinal studies.